Memristive Voltage Divider: A Bipolar ReRAM-based Unit for Non-Volatile Flip-Flops - Biglari, Mehrdad; Fey, Dietmar (MEMSYS'17 Proceedings of the International Symposium on Memory Systems, 2017)
Hibernation is the key mechanism for enabling normally-off and transient computing. The speed and energy dissipation of hibernation directly impacts the efficiency of the systems employing such computing paradigms. CMOS-compatible emerging memory technologies such as ReRAM provide non-volatile flip-flops (NvFFs) that realize fast and energy efficient hibernation using in-place store/restore. This paper presents memristive voltage divider (MVD), a non-volatile unit for NvFFs. Compared to conventional dual ReRAM units, MVD enables 67% reduction in energy dissipation and 36% reduction in store time, which translates into 79% reduction in the energy-delay product. MVD also remedies the endurance and variability concerns of ReRAM by providing read-while-write capability that enables low-overhead, fast, and energy efficient write verification mechanisms for NvFFs. As proof of concept, we also demonstrate an exemplar NvFF architecture using MVD for which energy dissipation trend in store and restore operations are reported.
Keywords: memristive voltage divider; memristor; non-volatile flip-flop; non-volatile unit; reram